2008
DOI: 10.1007/s00404-008-0634-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of enormous bilateral mucinous cystadenomas of the ovaries with abdominal plastic reconstruction

Abstract: Huge intraabdominal tumors that almost double a patient's body weight can hardly be malign. Total tumor excision is necessary because the heterogeneous composition requires careful examination by pathologists to rule out borderline tumors and non-invasive carcinomas. After tumor excision an abdominal wall reconstruction might be necessary because of the laxity and redundancy of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A review of 20 cases with lesions exceeding 20 kg confirmed a low malignancy rate [2]. Other authors also concur, stating that huge intra-abdominal tumors that almost double a patient’s body weight can hardly be malignant [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 20 cases with lesions exceeding 20 kg confirmed a low malignancy rate [2]. Other authors also concur, stating that huge intra-abdominal tumors that almost double a patient’s body weight can hardly be malignant [13].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively, reducing ileus, providing respiratory support, supporting abdominal wall tension, and monitoring hemodynamic parameters are key [2]. After tumor excision, an abdominal wall reconstruction might be necessary because of the laxity and redundancy of the skin [13]. We planned reconstructive surgery of the anterior abdominal wall after initial postoperative recovery because the patient was unstable at primary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Paracentesis in these settings carries increased peritoneal risks and complications. 18,19 Imaging studies (ultrasound, CT scanning, and/or magnetic resonance imaging [MRI]), therefore, are important for establishing the diagnosis and, in addition, may reveal additional findings, such as the presence of a displaced bowel, fluid levels, or a pseudocyst with clear borders (sometimes with endocystic partitions and vegetations).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported cases of huge ovarian mass are benign, mucinous cystadenoma [ Table 1 ]. [ 3 4 5 6 7 8 9 ] It is quite uncommon for a malignant ovarian tumor to be presented as a huge abdominal mass; primary care physicians should be vigilant not to miss an ovarian malignancy as one of the possible causes and should not delay referral to the gynecologist or oncologist.…”
Section: Introductionmentioning
confidence: 99%